2018
DOI: 10.3389/fmicb.2018.02224
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Lysis-Extraction Method Combined With IS6110-Amplification for Detection of Mycobacterium tuberculosis in Paucibacillary Sputum Specimens

Abstract: Background: When available, nucleic acid tests (NATs) offer powerful tools to strengthen the potential of tuberculosis (TB) diagnosis assays. The sensitivity of molecular assays is critical for detection of Mycobacterium tuberculosis (MTB) in paucibacillary sputum.Materials and Methods: The impact of targeting repetitive IS6110 sequences on the PCR sensitivity was evaluated across mycobacterium strains and reference material. Six lysis-extraction protocols were compared. Next, 92 clinical sputum specimens incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Furthermore, in this study a Chelex®‐based method was used for extraction of HSV and MTB DNA. This method is rapid, efficient with a low risk for laboratory‐induced contamination since all the procedure can be carried out in a single tube as recently reported . The expense for Chelex® method is very low as compared to the commercial methods based on silica columns or magnetic beads costing from 2 to 6$ per test, which makes it particularly advantageous in low‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study a Chelex®‐based method was used for extraction of HSV and MTB DNA. This method is rapid, efficient with a low risk for laboratory‐induced contamination since all the procedure can be carried out in a single tube as recently reported . The expense for Chelex® method is very low as compared to the commercial methods based on silica columns or magnetic beads costing from 2 to 6$ per test, which makes it particularly advantageous in low‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown M. tuberculosis isolates with lower number of IS6110 copies, this genomic marker is considered one of the best options to increase the sensibility of diagnostic tests. Indeed, the inclusion of the genomic sequences IS6110 and S1081 in the new generation of the GenXpert MTB/Rif test resulted in increased sensibility [31][32][33][34][35][36].…”
Section: Plos Onementioning
confidence: 99%
“…Although the CRISPR platform does not seem to solve the problem of specimen collection and the paucibacillary feature, its superior sensitivity and low LOD make this novel technology promising in detecting trace MTB in pediatric specimens. Combined with reasonable sample-pre-processing methods (Kolia-Diafouka et al, 2018), CRISPR platforms make it possible to reduce the volume of specimen that needs to be collected, and use noninvasive, easily accessible specimens instead of conventional ones to detect TB. Another research (Xiao et al, 2020) using Cas12a trans-cleavage has successfully identified MTB and six major nontuberculous mycobacteria (NTM) species, allowing the application of this method in the field of rapid MTB identification.…”
Section: Supporting Evidencementioning
confidence: 99%